(untitled) (Jurnal Teknologi (Sciences & Engineering), 2014)
Structural strength is just as important as any other measures for a performance vehicle - let it be in air, land or water. Chassis is the most critical constituent in keeping the integrity of a vehicular structure. Likewise, helicopter chassis is like its skeleton. Devoid of it, the helicopter will neither take shape nor conserve the structural strength necessary. This research took the liberty of appraising the structural stiffness of the chassis for UTM Single-Seat Helicopter which is being developed at Universiti Teknologi Malaysia (UTM). This helicopter uses space frames as the main chassis structure. The material used for this chassis is AISI 4130 steel. Static analysis of the chassis was conducted specifically during hovering condition. The analysis started with modelling and simulating the chassis using Finite Element Analysis (FEA) software. Data obtained through FEA simulation were then tested and verified using the experimental data. The results obtained were intriguing and in line with the FAA standard Regulation. Â Â